Primary tooth eruption in preterm low birth weight children - Palupi, Nadia Putri; Amalia, Rosa; Priyono, Bambang; Hanindriyo, Lisdrianto; Santoso, Aloysia Supartinah (Majalah Kedokteran Gigi Indonesia, 2025)
Primary teeth play a vital role as masticatory organs that support the digestive process in children. Preterm low birth weight (PTLBW) is a significant public health concern in many countries and may adversely affect children’s overall health. Understanding the patterns and timing of primary tooth eruption in PTLBW children is important, as it can provide valuable insights for clinical management, including the monitoring of dental development and the implementation of early interventions. This study presents a comprehensive scoping review of the literature on PTLBW and primary tooth eruption. The review followed the framework proposed by Arksey and O’Malley and was further refined using the Joanna Briggs Institute (JBI) methodology for scoping reviews. Literature searches were conducted in electronic databases, including Scopus and PubMed, covering publications from the past 10 years. Eight studies met the inclusion criteria and were analyzed in this review. The findings indicate that PTLBW children experience delayed eruption of primary teeth. Future prospective studies are needed to identify potential biomarkers or predictive indicators for delayed eruption, as well as to evaluate the effectiveness of early treatment interventions on dental development and oral health outcomes in this population.